Philosophical religions from Plato to Spinoza: reason, religion, and autonomy - Fraenkel, Carlos (Cambridge University Press, 2012)
"For many thinkers from Antiquity until the Enlightenment, no meaningful distinction between philosophy and religion was possible. Instead, the concept of a philosophical religion was strongly influential on pagan, Jewish, Christian and Muslim philosophers alike. Carlos Fraenkel provides the first account of this concept and traces its history back to Plato, the Jewish Philo of Alexandria and the Christians Clement of Alexandria and Origen. He then follows it through the medieval period in both Islamic and Jewish forms; he closely analyses its appearance in the work of Spinoza in the early modern period; and he shows how it largely disappeared after the Enlightenment, when religion began to be increasingly regarded as a promoter of ignorance and superstition from which philosophy needed to be liberated. His rich and wide-ranging book will appeal to anyone interested in how philosophy has interacted with Jewish, Christian, and Muslim religious traditions over the centuries"--